(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2025)
Using the laws of fluid mechanics for gases and treating atoms as vibrating strings subjected to gas and photon pressure, a useful expressions for cooling conditions was found. These conditions can be applied to nano and quantum systems as far as the model recognises the particle dual nature, which is the cornerstone of quantum physics. These expressions indicated that the atoms density and the degree of cooling, as well the photon density and frequency, affected the cooling process. Dense and high cooling degree requires increasing the applied photon density or the frequency or both.